Examining Deductive Versus Guided Instruction From an Interactionist Perspective. Issue 1 (15th February 2022) - Azkarai, Agurtzane; Oliver, Rhonda; Gil‐Berrio, Yohana
Abstract: The interactionist hypothesis holds that conversational interaction facilitates second language (L2) learning by providing learners opportunities to receive meaningful input, modify their output, and attend to language form. Although research has often explored the efficacy of different types of L2 instruction (deductive or inductive), few studies have done so from an interactionist perspective. This study explores small‐group interactions of 19 L2 Spanish learners from two intact high school classes as they completed four communicative tasks following either deductive or PACE instruction on the pronoun se . We examined the nature of the student group interactions in each class, focusing on negotiation of meaning (NoM) strategies and language‐related episodes (LREs). The deductive participants used more NoM strategies, and produced more LREs than PACE participants. Regardless of the type of instruction, the majority of LREs dealt with vocabulary and were resolved correctly. Task conditions also mediated the outcomes of feedback and LREs. Abstract :